Effect of crossbreeding with Limousine, Rubia Gallega and Belgium Blue on meat quality and fatty acid profile of Holstein calves. (23rd February 2015) - Domingo, Gonzalo; Iglesias, Antonio; Monserrat, Lorenzo; Sanchez, Luciano; Cantalapiedra, Jesus; Lorenzo, Jose Manuel
Abstract The object of this work was to study the effects of crossbreeding on meat quality and fatty acid profile of Holstein calves. Samples were taken from Longissimus thoracis (LT) muscle of 36 calves of three different groups (Holstein crossed with Rubia Gallega (HF×RG), Holstein crossed with Limousine (HF×LI) and Holstein crossed with Belgian Blue (HF×BB)). Significant differences were observed in carcass weight and killing out percentage (P < 0.001) among, groups reaching the highest values in the HF×BB group (228 kg and 59.4%, respectively), while the cross with Limousine presented the lowest values for carcass weight (191 kg) and the cross with Rubia Gallega showed the lowest killing out percentages (54.9%). Meat from HF×RG animals was redder (a* 13.31) and lightest (L* 39.55) than meat from HF×LI and HF×BB groups. With regard to fatty acid profile, the saturated fatty acids were the most abundant fatty acid, followed by monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids in the three groups. Crossbreeding did not affect the proportion of fatty acid. Finally, live weight, cold carcass weight, killing out, shear force, L* from LT, b*from LT, a* from fat, b* from fat, C14:0, C15:0, C16:0, C18:0, C18:3n‐6, MUFA and price‐to‐sales ratio were the selected variables from discriminant analysis to classify the types of crossbreeding.